Factors Related to Passive Social Withdrawal and Active Social Avoidance in Schizophrenia. Issue 7 (7th July 2022) - Farina, Emily A.; Assaf, Michal; Corbera, Silvia; Chen, Chi-Ming
Abstract: Social withdrawal in schizophrenia may be a result of "passive" motivation (reduced drive to engage) or "active" motivation (increased drive to avoid). We conducted a cross-sectional, between-subjects study using self-report measures and social cognition tasks to evaluate the relationships between motivational subtypes, social abilities, and social functioning in schizophrenia spectrum ( n = 52, ages 19–34). Regression models showed significant differences in passive and active withdrawal. Passive, but not active, motivation predicted social functioning as measured by a clinical interview. This suggests that motivation, especially passive type, plays an important role in social withdrawal in schizophrenia. However, on a self-report measure of social functioning, neither passive nor active motivation predicted outcomes, suggesting a potential disconnect between observer versus self-report measures when assessing social motivation. Furthermore, performance on tasks of social abilities did not predict motivation, which supports the idea that motivation is distinct from social ability and should be specifically addressed in treatment.